In vitro pharmacoregulation of CC chemokine ligand 5 and its receptor CCR5 in diffuse lung diseases - Sekerova, Veronika; Subrtova, Daniela; Mrazek, Frantisek; Gibejova, Agata; Kolek, Vitezslav; du Bois, Roland M; Petrek, Martin (Mediators of inflammation, 2003)
BACKGROUND: CC chemokine ligand (CCL)5 and its receptor CCR5 contribute to leukocyte migration into lungs of patients with diffuse lung diseases (DLD). Pharmacological regulation of CCL5 and CCR5 expression was therefore explored in bronchoalveolar cells obtained from patients with DLD. METHODS: Cells from 21 patients were co-cultivated in vitro with tumour necrosis factor-alpha and dexamethasone, cyclosporin A (CyA) or pentoxifylline. Chemokine mRNA expression and protein production was assessed by reverse transcription-polymerase chain reaction and enzyme-linked immunosorbent assay, respectively. RESULTS: Dexamethasone altered CCL5 mRNA expression and suppressed its protein levels. CyA inhibited chemokine mRNA expression but not protein production. Pentoxifylline did not affected chemokine expression. Both dexamethasone and CyA suppressed CCR5 mRNA transcripts. CONCLUSION: In conclusion, while dexamethasone downregulates the CCL5 functional form, CyA and pentoxifylline have no effects on CCL5 protein. These data provide in vitro correlation for clinical applications of immunomodulators in therapy of DLD.
Keywords: senioři; cyklosporin; kultivované buňky; messenger RNA; Chemokine CCL5; Immunosuppressive Agents; Leukocytes; Cyclosporine; chemokiny CC; plicní nemoci; Tumor Necrosis Factor-alpha; Glucocorticoids; Pentoxifylline; Middle Aged; mužské pohlaví; glukokortikoidy; Adult; bronchoalveolární lavážní tekutina; TNF-alfa; Cells, Cultured; Lung Diseases; Receptors, CCR5; ženské pohlaví; RNA, Messenger; imunosupresiva; Humans; receptory CCR5; dexamethason; Bronchoalveolar Lavage Fluid; pentoxifylin; lidé středního věku; Chemokines, CC; chemokin CCL5; Dexamethasone; dospělí; Female; Aged; leukocyty; Enzyme Inhibitors; lidé; Male; inhibitory enzymů